2018
DOI: 10.1002/gps.4951
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic hypotension in patients with late‐life depression: Prevalence and validation of a new screening tool

Abstract: OH is common in patients with LLD conferring them a risk of gait instability and falls. Females had a higher risk of having OH while participants who were married or in a common-law relationship were less likely to have OH. Although the OHQ is a quick to administer paper-based screening test, it did not show adequate diagnostic accuracy in patients with LLD seen in a routine psychiatry clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
1
0
1
Order By: Relevance
“…Снижение мобильности является предиктором формирования зависимости от помощи окружающих, инвалидизации, когнитивного снижения, падений, госпитализаций, повышает риск смерти [18]. Выявлена ассоциация между низкой скоростью ходьбы по данным самоотчета пациентов и низким качест вом жизни, а также наличием симптомов депрессии [19]. Снижение мобильности может служить чувствительным предиктором состояния здоровья пожилых людей и важным параметром при определении объема необходимого ухода.…”
Section: хронические неинфекционные заболевания ассоциирующиеся с орunclassified
“…Снижение мобильности является предиктором формирования зависимости от помощи окружающих, инвалидизации, когнитивного снижения, падений, госпитализаций, повышает риск смерти [18]. Выявлена ассоциация между низкой скоростью ходьбы по данным самоотчета пациентов и низким качест вом жизни, а также наличием симптомов депрессии [19]. Снижение мобильности может служить чувствительным предиктором состояния здоровья пожилых людей и важным параметром при определении объема необходимого ухода.…”
Section: хронические неинфекционные заболевания ассоциирующиеся с орunclassified
“…Studies on individuals with chronic SCI have identified blood pressure instability as one of the determinants of cardiovascular morbidity and mortality, including a 4-fold increased stroke risk in the SCI population (Su and Miao, 2005;Jegede et al, 2010;Rothwell et al, 2010;Wu et al, 2012;Muntner et al, 2015;Piatt et al, 2016;Stevens et al, 2016;Parati et al, 2018;Ditterline et al, 2020;Parati et al, 2020). Even in those without SCI, mounting evidence links blood pressure instability during orthostasis with poorer general physical and mental health (Wilkie et al, 1976;Wessely et al, 1990;Pilgrim et al, 1992;Rosengren et al, 1993;Barrett-Connor and Palinkas, 1994;Czajkowska et al, 2010;Vasudev et al, 2011;Regan et al, 2013;Briggs et al, 2016;Briggs et al, 2018;Shanbhag et al, 2018).…”
Section: Introductionmentioning
confidence: 99%